Good Practices in Transitional Care: continuity of care for patients undergoing liver transplantation - Laísa Fischer Wachholz; Neide da Silva Knihs; Suyan Sens; Sibele Maria Schuantes Paim; Aline Lima Pestana Magalhães; Bartira de Aguiar Roza (Revista Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to develop a guide of care recommendations for good practices in care transition for adult patients undergoing liver transplantation. Methods: a methodological study, based on the Appraisal of Guidelines for Research & Evaluation in the updated version, II. Care recommendations were sustained by conducting an integrative literature review and qualitative research. Results: from evidence, three topics emerged: Care Transition Planning; Health Education for Self-Care; Care Management. Each of the central topics has respective subtopics, totaling six, giving rise to 30 care recommendations. Concerning evaluators’ scores, in all domains the scores were higher than 90%. Final Considerations: the proposed guide assists professionals in conducting care transition in liver transplantation, ensuring greater safety for patients in continuity of home care.